Effectiveness of Biolarvicide Extract and Granule Formulation of Cocok Bubu Leaves Against Aedes aegypti - Hayati, Mila Nurmala; Khumaisah, Lela Lailatul; Anwar, Devi Indah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Dengue Hemorrhagic Fever (DHF), transmitted by Aedes aegypti, remains a major public health concern. This study aims to evaluate the effectiveness of biolarvicides from methanol and acetone extracts of cocok bubu (Elatostema rostratum) leaves and their granule formulations. Extracts and granules were tested at concentrations of 50, 100, 200, and 400 ppm. Granule preparations met standard criteria, including organoleptic properties, active compound content, and dispersion time. The analysis included LC₅₀ and LT₅₀ determination for both extract types. The acetone extract showed greater larvicidal activity (LC₅₀ = 85.67 ppm; LT₅₀ = 51.1 hours) than the methanol extract (LC₅₀ = 112.854 ppm; LT₅₀ = 51.8 hours), both falling into the moderate-to-high toxicity category. Similarly, the granule formulations showed that acetone-based granules (LC₅₀ = 496.941 ppm; LT₅₀ = 51.1 hours) were more effective than methanol-based granules (LC₅₀ = 528.774 ppm; LT₅₀ = 57.3 hours), with moderate-to-low toxicity. These findings indicate that cocok bubu leaf extracts, particularly acetone-based, have potential as effective plant-derived larvicides. Further development of plant-based larvicides may offer safer alternatives to synthetic larvicides in vector control programs.